Voice hearers' experiences of the Making Sense of Voices approach in an NHS setting. Issue 2 (2nd April 2020) - Steel, Craig; Schnackenberg, Joachim; Travers, Zoe; Longden, Eleanor; Greenfield, Emily; Meredith, Lynette; Perry, Hayley; Corstens, Dirk
ABSTRACT: The 'Making Sense of Voices' (MsV), or 'Maastricht' approach has become established within large sections of the voice hearing community, as well as being adopted by some professional mental health workers. However, there has been limited research to assess this intervention. A recent case series using the MsV approach reported promising results across a number of standardised outcome measures. The current study reports on the voice hearers' experience of having received the MsV intervention, through the use of "exit interviews" conducted as part of the case series. Individual participants' experiences indicated a range of reactions to the intervention. Positive outcomes appeared to relate to a better understanding of voice hearing experiences and a greater sense of control over voices. Not all participants reported a positive experience of communicating with their voices. Outcomes are discussed within the context of potential common and distinct "ingredients" of the MsV approach, compared to other approaches to working with distressing voices.